Unveiling the complex electronic structure of amorphous metal oxides - Ãrhammar, C; Pietzsch, Annette; Bock, Nicolas; HolmstrÃ¶m, Erik; Araujo, C. Moyses; GrÃ¥sjÃ¶, Johan; Zhao, Shuxi; Green, Sara; Peery, T; Hennies, Franz; Amerioun, Shahrad; FÃ¶hlisch, Alexander; et al. (Proceedings of the National Academy of Sciences - PNAS, 2011)
Amorphous materials represent a large and important emerging area of material's science. Amorphous oxides are key technological oxides in applications such as a gate dielectric in Complementary metal-oxide semiconductor devices and in Silicon-Oxide-Nitride-Oxide-Silicon and TANOS (TaN-AlâOâ-SiâNâ-SiOâ-Silicon) flash memories. These technologies are required for the high packing density of today's integrated circuits. Therefore the investigation of defect states in these structures is crucial. In this work we present X-ray synchrotron measurements, with an energy resolution which is about 5-10 times higher than is attainable with standard spectrometers, of amorphous alumina. We demonstrate that our experimental results are in agreement with calculated spectra of amorphous alumina which we have generated by stochastic quenching. This first principles method, which we have recently developed, is found to be superior to molecular dynamics in simulating the rapid gas to solid transition that takes place as this material is deposited for thin film applications. We detect and analyze in detail states in the band gap that originate from oxygen pairs. Similar states were previously found in amorphous alumina by other spectroscopic methods and were assigned to oxygen vacancies claimed to act mutually as electron and hole traps. The oxygen pairs which we probe in this work act as hole traps only and will influence the information retention in electronic devices. In amorphous silica oxygen pairs have already been found, thus they may be a feature which is characteristic also of other amorphous metal oxides.